(untitled) (Orfeu, 2017)
This text presents a discussion of Brazilian composer José Vieira Brandão´s (1911-2002) attitudes towards the Brazilian nationalist movement as well as his engagement with this trend as shown in his theoretical/analytical writings presented as a Docent Thesis in 1949. Brandãos´s posture is clearly expressed in his compositions. This particular analysis focuses on Tocata n° 1 (Etude n° 4) dedicated to Villa-Lobos, eminent representative of the nationalist modernist aesthetics. Considering how closely Brandão worked with Villa-Lobos as his preferred pianist, we aim at revealing shared sociocultural and musical concerns. With this purpose in mind, we evoke Agawu´s (2009) topics adapted to the analysis of Latin American music by Plesch (1996) and to Brazilian music by Piedade (2013). Our analysis of this work seeks to reveal how Brandão´s “new aesthetics trends” (BRANDÃO, 1949) is a musical reification of the Brazilian nationalist ideology. Our reading of Brandão´s Tocata n°1 with its characteristic elements of Brazilian music, considers the work not only as a deeply felt homage to his mentor Villa-Lobos but also as a legitimate representative of the political and artistic zeitgeist.